2015
DOI: 10.1017/s0007114515001038
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and growth factor profiling in patients with the metabolic syndrome

Abstract: The metabolic syndrome (MetS) is associated with a pro-inflammatory milieu that may partially account for its association with an increased cardiovascular risk. We aimed to (1) evaluate the serum concentrations of twelve cytokines and growth factors (epidermal growth factor (EGF), interferon-g (IFN-g), IL-1a/-1b/-2/-4/-6/-8/-10, monocyte chemoattractant protein-1 (MCP-1), TNF-a and vascular endothelial growth factor (VEGF)) in 303 individuals with or without the MetS; and (2) explore their relationship with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 46 publications
7
50
1
1
Order By: Relevance
“…These findings were consistent with those in previous reports in adults [13,16]. Moreover, the serum concentrations of CXCL10 were significantly correlated with obesityrelated metabolic abnormalities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings were consistent with those in previous reports in adults [13,16]. Moreover, the serum concentrations of CXCL10 were significantly correlated with obesityrelated metabolic abnormalities.…”
Section: Discussionsupporting
confidence: 93%
“…Ito et al showed that CC motif ligand 2 (CCL2, monocyte chemoattractant protein; MCP-1)/ CC motif receptor 2 (CCR2) pathway plays a role in macrophage infiltration into obese adipose tissue and obesity-related MS [12]. Previous studies [13][14][15] reported that the levels of CCL5 are elevated in obese adults with MS. Additionally, Faber et al reported that CXC motif chemokine 10 (CXCL10, interferon gamma-induced protein 10; IP-10) was related to VAT accumulation in adults [16]. Accumulating evidence suggests that these chemokines play important roles in the formation of MS in adult.…”
mentioning
confidence: 99%
“…This confirms previous studies showing that well-controlled diabetes is not associated with increased levels of VEGF [23,24]. Moreover, others and we have shown previously that serum VEGF-A increases with increasing HbA1c [8,11].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, CTAD plasma VEGF-A levels were lowest, followed by PECT- and EDTA-plasma. Moreover, we and others confirmed earlier that serum VEGF-A levels are largely higher relative to plasma levels in patients with type 1 and 2 diabetes, metabolic vascular syndrome, different malignancies and rheumatoid arthritis [4,8,9,11,23,24,26–29]. …”
Section: Discussionsupporting
confidence: 90%
“…The proinflammatory effects of excess adipose tissue are a hallmark of MetS 12 , which itself is a cluster of metabolic disorders that includes abdominal obesity, hypertension, lowered high density lipoprotein (HDL) cholesterol, elevated triglycerides, and elevated fasting glucose 13 . MetS is a better predictor of total mortality than its individual components 14 , and may increase the risk of BE 1518 and EA 19 .…”
Section: Introductionmentioning
confidence: 99%